Development and validation of a high performance liquid chromatography method to determine nevirapine in plasma in a resource-limited setting - Faithful Makita-Chingombe; Andrew J. Ocque; Robin DiFrancesco; Charles Maponga; Farai Muzambi; Tsitsi G. Monera-Penduka; Tinashe Mudzviti; Takudzwa J. Mtisi; Gene D. Morse (AOSIS, 2019)
Background: There are several instances where nevirapine pharmacokinetic monitoring may be useful, such as in special populations or pharmacokinetic drug interaction studies that require the ascertainment of nevirapine pharmacokinetics in the sub-Saharan region. Objectives: The main aim of this study was to produce a validated, sustainable and relevant nevirapine assay method that meets bio-analytical regulatory requirements. Methods: The developed method utilised a Waters 2795 Alliance high performance liquid chromatography system with a 2996 photo diode array detector, an Atlantis dC18 5 micron, 3.9 mm × 150 mm analytical column and a gradient flow rate of 1 mL/min. Ultraviolet detection data were collected from 210 nm to 400 nm, extracted at 260 nm, and processed for nevirapine and internal standard peak height responses. Results: The method proved to be linear (R2 0.995), precise (+1.92% - +9.69%) and accurate (-9.70% - 12.0%). Recovery for the analyte and internal standard was between 98.8% and 114%. The method showed good specificity as no interferences were caused by common African traditional medicines, anti-tuberculosis medications or other concomitant antiretrovirals nor endogenous components. Conclusion: The method is reproducible, relevant to our setting and uses considerably low plasma volumes with preservation of some consumables, a desirable key factor in a resource-limited setting.